(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The development of important factors of ecotourism in Uzbekistan and the specifics of more efficient use of architectural and landscape factors are described. And also the features, factors of development and the socio-economic essence of ecotourism are studied. The state of development of tourism in Uzbekistan, the potential and level, as well as the development of architectural and landscape mechanisms of ecotourism in the regions are analyzed.